Anthropometric predictors of dyslipidemia among adults in Saudi Arabia - Abdalla A Saeed (Epidemiology, Biostatistics and Public Health)
Background: dyslipidemia and obesity are key independent modifiable risk factors for many non communicable chronic diseases. Patterns of association between these factors may help prevention and control. This study aims to assess the association between lipids profile and obesity among adults in Kingdom of Saudi Arabia and identify anthropometric predictors of dyslipidemia. Methods: data were collected and analyzed from a cross-sectional study using WHO STEPwise approach that included 4 990 Saudi adults aged 15- 64 years selected by stratified, multistage, cluster random sampling technique. Lipid profiles (cholesterol categories and triglycerides) were determined spectrophotometrically by colorimetric biochemical methods. Obesity was determined by calculation of body mass index (BMI=Kg/m2), waist and hip circumferences and ratio and waist to height ratio. Results: the overall prevalence of obesity ranged from 33.8 to 44.4 % and the overall dyslipidemia prevalence ranged from about 25 to 44% depending on type of dyslipidemia and anthropometrics used. Prevalence of dyslipidemia and mean concentration of lipids profile were generally significantly higher in obese than non obese. The indicator waist/height ratio was the significant predictor for all types of dyslipidemia and all levels of serum lipids. Conclusions: the prevalence dyslipidemia and obesity are high and they are positively associated. Waist/height ratio was the most important predictor of dyslipidemia among adults.